Confinement in bending of high-strength lightweight aggregate concrete beams. (May 2022) - Zivkovic, Jelena; Arve Øverli, Jan
Abstract: The use of lightweight aggregate concrete (LWAC) is limited as a mainstream construction material in structural applications due to more brittle post-peak material behavior and uncontrolled crack propagation compared to normal density concrete (NWC). To improve the ductility of LWAC structures, the confinement effect from the transverse reinforcement in conjunction with longitudinal reinforcement was considered. In addition, it was tested the influence of concrete cover. The ultimate compressive strain at peak load was approximately 3.5‰ for all beams, which is like the level expected for NWC. It is possible to increase the ductility of LWAC structures by appropriate reinforcement detailing.